The Firestone Patented Gum Dipping Process in the Fireston Factory and Exhibition Building, A Century of Progress (R.R. Donnelley & Sons Co.)
By this process, eight extra pounds of rubber are added to every one hundred pounds of high-stretch cord, coating every fiber in every cord. This is an extra process for Safety, Strength, and Durability - not used in any other tire. Gum-Dipped High-Stretch Cords withstand road shocks 58% longer - and the Two Extra Gum-Dipped Cord Plies under the Tread give 56% greater bond between Tread and Cord Body.